1991
DOI: 10.1042/bj2780255
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cytosolic Ca2+, sn-1,2-diacylglycerol and inositol 1,4,5-trisphosphate elevation in platelet-activating-factor-stimulated rabbit platelets. Influence of protein kinase C on production of signal molecules

Abstract: The temporal and dose-response relationships of platelet-activating-factor (PAF)-induced changes in the concentrations of cytosolic Ca2+ ([Ca2+]i), Ins(1,4,5)P3 and 1,2-diacylglycerol (DAG) were examined. In addition, phosphorylation of protein kinase C (PKC) substrate (40-47 kDa protein) was determined. In high-dose PAF-activated platelets, all three signal molecules increased rapidly and transiently, with the peak Ins(1,4,5)P3 concentration preceding maximal elevation of [Ca2+]i by 5 s. In low-dose PAF-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 57 publications
(34 reference statements)
3
33
0
Order By: Relevance
“…platelet responses such as aggregation and degranulation [2-51. We note that Murphy et al [4] reported no effect for 1 PM staurosporine on Ins(1,4,5)P, in rabbit platelets. Species differences may account for the difference in results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…platelet responses such as aggregation and degranulation [2-51. We note that Murphy et al [4] reported no effect for 1 PM staurosporine on Ins(1,4,5)P, in rabbit platelets. Species differences may account for the difference in results.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, initial increases in [Ca2+]i triggered by platelet agonists are amplified by phospholipase A2 activation and TXA, formation [20-221. It is possible that staurosporine failed to activate the amplification pathway or that it blocks amplification at an early step. Direct staurosporine inhibition of TXA, synthesis can be ruled out since 1 PM staurosporine has been shown to enhance thromboxane formation in platelets stimulated by platelet activating factor [4]. The mechanism by which staurosporine activated PLC in platelets remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…damage produced by ischemia/reperfusion (Lobner and Lipton, 1993;Zaidan and Sims, 1994). PAF receptor stimulation is known to increase intracellular Ca 2~, both via its release from intracellular stores and by its influx through the cell membrane (Kornecki and Ehrlich, 1991;Murphy et a!., 1991;Bito et a!., 1992;Kamata et al, 1993). We therefore examined the role of Ca2~in PAF-mediated ischemia/ reincubation-induced cell damage.…”
Section: Role Of Calcium In Ischemia/reincubation-induced Cell Deathmentioning
confidence: 99%
“…To terminate TxB, generation, sub-samples of platelets (400 pl) were withdrawn 3 min after PAF addition and added to 40 pl icecold 100 mM EDTA and 30 pM indomethacin. The samples were centrifuged at 8000 X g for 2 min, the supernatant removed and the TxB, content determined by radioimmunoassay (Johnston et al, 1984) as we have previously described (Murphy et al, 1991). The sensitivity of the assay was CO.1 pmol TxB,/108 platelets.…”
Section: Measurement Of Txb Generationmentioning
confidence: 99%
“…The samples were centrifuged at 8000X g for 2 min, then 2 X 100 p1 samples of the supernatant were removed and the amount of 5-H['4C]T determined by liquid scintillation spectroscopy. The 5-H['4C]T release was determined as previously described (Holmsen and Dangelmaier, 1989 ;Murphy et al, 1991).…”
Section: Measurement Of the Percentage 5-hydro~y['~c]tryptamine Releasementioning
confidence: 99%